Implementasi Model Shared Christian Praxis Dalam Kelompok Sel Untuk Meningkatkan Pertumbuhan Iman Mahasiswa TransformNation Malang - Zebua, Eniwati; Usmany, Janneman (STIPAK Malang, 2025)
The Shared Christian Praxis model is one of the approaches to religious education that combines theological reflection with life experiences, enabling students to be actively involved in faith growth through five main steps: 1) Sharing life experiences based on themes, 2) Analyzing and reflecting on life experiences theologically, 3) Discussing the Word of God, 4) Planning the implementation to be carried out, and 5) Concluding the discussion to act. This study aims to evaluate the implementation of the Shared Christian Praxis model developed by Thomas Groome in cell groups (KOMSEL) to improve the faith growth of TransformNation students in Malang. The method used by the researcher is qualitative with a phenomenological approach, using triangulation data collection techniques: semi-structured interviews, observation, and documentation. The objects of the study were participants in the TransformNation Malang student cell groups. The results of the study indicate that the application of the Shared Christian Praxis model in komsel is one way that can significantly increase students’ faith growth. The results of interviews and observations showed an increase in theological understanding and positive changes in student behavior and spirituality. This model is effective as a method of teaching theology with thorough preparation, and flexibility in discussion topics, and helps create a supportive and inclusive community, where each member feels accepted and encouraged to share and learn together. Based on the results of the research that have been presented, the recearcher provides several suggestions, namely: 1) Cell group leaders need to receive intensive and ongoing training, 2) Effective strategis to increase student participation need to be implemented, 3) Periodc evaluation and feedback from students need to be carried out to Shared Christian Praxis model.